Extraction and characterization of cushuro (Nostoc sphaericum) polysaccharides - Chasquibol Silva, Nancy Ascención (2025)
Cushuro (Nostoc sphaericum) is a blue-green edible freshwater microalgae of ancestral use as a traditional food in the Andean regions of Peru. Knowledge of the extraction process conditions and characteristics of cushuro biomass polysaccharides are instrumental to expand its range of applications and appraise its potential utilization as a hydrocolloid ingredient in food and other applications. Polysaccharides acid extract (PCAcE) and polysaccharides aqueous extract (PCAqE) with hot water at 90 °C were extracted from cushuro (Nostoc sphaericum) biomass collected from the Department of Ancash, Peru. PCAcE showed higher extraction yield (49.0 ± 0.5 %), purity (83.3 ± 0.3 %), emulsifying capacity (55.6 ± 1.0 %), foaming capacity (8.3 ± 0.3 %), water holding capacity (3.0 ± 0.11 g/g) and DPPH radical scavenging activity (73.0 %) than PCAqE. Also, FTIR spectra showed a typical polysaccharides’ fingerprint. PCAcE showed a Mw of 1.0 ± 0.4 × 105 Da, dispersity index (Ð) of 3.5 ± 0.4, radius of gyration (Rg) of 22 ± 5 nm and a branched-type conformation, characterized by multi-detection HPSEC. The monosaccharide composition of PCAcE consisted mainly of glucose, xylose and galactose, and lower amounts of rhamnose. The rheological properties in aqueous solution, investigated under sensitive small-deformation oscillatory rheometric, revealed that the polysaccharide acidic extract (PCAcE) showed “weak gel” properties, unexpected on a typical highly branched polysaccharide. These results suggest potential applications of cushuro (Nostoc sphaericum) polysaccharides as a viscosity enhancer and natural emulsifier to stabilize oil-water emulsions in foods and other applications.